A multiscale wear model for reciprocating rod stepseal under mixed lubricating conditions based on linear elasticity. (January 2021) - Ran, Hongliang; Wang, Shaoping; Liu, Di
The macroscale simulation methods are commonly used to study the wear of reciprocating seals to analyze macroscopic effects on the seal wear. There is a lack of numerical method for analyzing the wear of reciprocating seal under mixed lubricating conditions. According to experimental studies, some microscopic factors, including lubrication characteristics and surface roughness, are important for wear of reciprocating seal. Hence, in the presented research, a numerical model is proposed to analyze the effects of microscopic factors on reciprocating rod stepseal wear. O-ring of the stepseal is considered to be hyper elastic, while Turcon ring of the stepseal, which directly contacts with rod surface, is assumed to be linear elastic. The effects of microscopic aspects, including lubrication characteristics, are highlighted and analyzed. Furthermore, the seal wears under different operating conditions are analyzed and discussed. The simulation results show that the seal wears during outstroke and instroke are different. With the rod speed increasing, the wear distance rate increases during outstroke, while decreases during instroke. The seal wear increases with the sealed pressure increasing and/or compression rate increasing. With the increase in the fluid viscosity, the wear of the seal increases during outstroke and decreases during instroke. With the increase in the seal surface roughness, the seal wear decreases during outstroke and increases during instroke.